Comparing the effectiveness of laser vs. conventional endoforehead lifting. (17th February 2018) - Chang, Cheng-Jen; Yu, De-Yi; Chang, Shu-Ying; Hsiao, Yen-Chang
ABSTRACT: The objective of this study was to compare the efficacy and safety of laser versus conventional endoforehead lifting. Over a period of 12 years (January 2000–January 2012), a total of 110 patients with hyperactive muscles over the frontal region have been collected for a retrospective study. The SurgiLase 150XJ CO2 laser system, in conjunction with the flexible FIBERLASE, was used. The endoscope was 4 mm in diameter with an angle of 30°. The primary efficacy measurement was the assessment of the final outcome for using laser vs. conventional methods. Both groups were observed at three weeks, six weeks and six months after surgery. The most common complication in early convalescence (three weeks) was swelling. This was followed by local paraesthesia, ecchymosis, localized hematomas and scar with alopecia. All these problems disappeared completely after the 6-month study period. Based on a chi-square analysis, there were clinically and statistically significant differences favouring the laser endoforehead surgery in the operative time, early and late complications. All patients achieved significant improvement after both laser and conventional endoforehead surgery in the final outcome. However, the early and late complications indicated a greater difference in the laser group.